Determination of Dinotefuran and Its Metabolites in Orange Pulp, Orange Peel, and Whole Orange Using Liquid Chromatography-Tandem Mass Spectrometry. (22nd November 2019) - Yang, Zaihui; Zhang, Kankan; Chen, Lingzhu; Liu, Bin; Zhang, Qingtao; Zhang, Haizhen; Sun, Caiyuan; Hu, Deyu
Abstract: Determination of the polar characteristics of dinotefuran and metabolite residues in orange matrixes (orange pulp, orange peel, and whole orange) is difficult. Thus, the purpose of the present study was todevelop an extraction method for the determination of dinotefuran and its metabolites in oranges by using liquid chromatography with tandem mass spectrometry (LC-MS/MS). Matrix suppression effects were observed for all analytes in the orange matrixes. The proposed method displayed satisfactory linearity (R 2 ≥ 0.9856) for the target molecules. The LODs were 0.03–0.10 mg/kg, whereas LOQs were 0.08–0.40 mg/kg for dinotefuran and its metabolites. Recoveries were 79.1–98.7% with RSD values <20% for all analytes in the orange matrixes. The proposed method was used to authenticate the samples and dinotefuran residues observed in field-incurred orange matrixes. The results of the proposed method could help the Chinese government establish maximum residue limits for dinotefuran in orangesand promote the safe and proper use of dinotefuran dosages in orange trees.